Forest Soil Characterisation with Reference to Clay Mineralogy and Natural Vegetation - Samra, J. S.; Singhal, R. M.; Banerjee, S. P.; Sharma, S. D. (Indian Forester, 1985)
Clay mineralogical characterisation of soils of four different natural vegetational sequences of South Kheri forest division has been attempted. Sand mineralogical analysis revealed that the soils have developed from the same source. Hence differences in their characteristics might have been triggered off by the diversity in their vegetative cover. Ellite was present in all the soils with different relative propositions. Vermiculite, mixed minerals and chlorite seem to be present in higher amount in Argiustolls, Haplustolla and Haplustalfs having more diversity in their natural vegetation. Ellite dominated in Ustochrepts under a purest and of Shorea robusta. More alteration of Ellite or neo-synthesis of vermiculite and chlorite seems to have taken in soils with comparitively wet soil moisture regims as evidenced from the natural groeth of moisture loving indicator species like Syzygium cumini and Terminalia alata.